The comparison between transurethral resection and electrovaporization in treatment of superfacial bladder tumors Recurrence - علي بري; محمد كنعان; أيمن حرفوش (Latakia University Journal -Medical Sciences Series, 2023)
Objective: The aim of the study is to compare between Transurethral resection and electrovaporization in treatment of superfacial bladder tumors in order to choose the best treatment. Methods: Study type: A Prospective Interventional Study The study was conducted of patients admitted in Urology department at Tishreen University Hospital during the period between 2022-2023, and they were diagnosed with bladder cancer. The patient was then subjected to endoscopic transurethral intervention under anesthesia and complete resection or electrovaporization for the tumor was done. A diagnostic biopsy was taken from the tumor and sent to histopathology. Then, periodic monitoring of the patient was applied to detect the presence of tumor recurrence after 3 months, 6 months, 9 months and 12 months. The results were compared between the aforementioned disease groups, and then we analyzed the data after being entered into the statistical program SPSS Version 26. Results: 150 patients were included in the study, of whom 30 patients were excluded who had invasive tumor and did not meet the entry criteria and only 120 patients were studied. The patients ages ranged between 52 and 76 years, with the average age being 63 years. The number of males in the study sample was 81 patients (67%), and the females were 39 patients (33%). The most common placement of the tumor in the patients of the sample studied was in the bladder wall, with a close ratio between the right and the left, with a slight preponderance in the right side, where the percentage (37%, or 44 patients) and (33%, or 40 patients) was in the left side of the bladder wall. The sizes of tumors in the study sample ranged between 1-5 cm and the distribution of patients was as follows: 18 patients (15%) 1 cm, 35 patients (29 %) 2 cm, 28 patients (24 %) 3 cm, 22 patients (18 %) 4 cm, 17 patients (14 %) 5 cm. Electrovaporization was performed on 41 patients (34%) and transurethral resection on 79 patients (66%). During the patient observation period over one year, the overall recurrence rate was 14% (17 patients), of which 4% (5 patients) underwent electrovaporization and 10% (12 patients) underwent transurethral resection. It was noted in the study sample that the size of the tumor does not play a significant role in affecting the rate of tumor recurrence. Conclusions: The study showed that both methods are reliable in the treatment of superficial bladder tumors, with a slight probability of electrovaporization in maintaining low recurrence rates, also there is a need to conduct periodic examination of the bladder for early detection of bladder tumors and its timely treatment.